Conceptualisation and validation of system use reduction as a self-regulatory IS use behaviour. Issue 1 (2nd January 2020) - Osatuyi, Babajide; Turel, Ofir
ABSTRACT: Focusing on social networking site (SNS) users, this research conceptualizes, theorizes on and tests information systems (IS) use reduction herein defined as users' attempt to reduce their use of an IS to levels that seem reasonable to them to avoid negative implications. IS use reduction is more realistic for many users than full discontinuance, more prevalent than many other corrective behaviors, and can have many desirable outcomes. Yet, knowledge regarding this behavior has been limited. It therefore warrants more attention in IS research and a growing need to develop interventions aimed at helping users reducing excessive IS use such as SNSs. We suggest that IS use reduction can be motivated by negative consequences of excessive SNS use and that the way users translate such states into SNS use reduction intentions can be explained by a contextual and nuanced adaptation of Bandura's self-regulation of motivation and self-reactive framework. A survey study (study 1, n=257) was used to theorize and test the determinants of SNS use reduction intentions, and a longitudinal experimental study (study 2, n=127) extended the validity of the survey study findings, established causality and examined whether the manipulation the survey study predictors can produce actual SNS use reduction.